The witch's apprentice - Elliott, Zetta (Elliott, Zetta. Dragons in a bag (Series), 2022)
Now that he is Ma's apprentice Jax is finding himself mixed up with all sorts of magical doings, like taking care of a phoenix egg which is going to hatch soon, trying to bring back the creatures Sis stole, finding his grandfather, and convincing Sis, the guardian, to reunite the two realms--and hopefully living to see Brooklyn again.